The Use of Youtube to Improve Listening Skills for Non-English Major Students in EFL Classroom - Erlinna Juita (Departement of Mathematics Education, 2024)
Compared to the four language skills, listening is the first language skill acquired by a language learner. Nevertheless, Students frequently had low performance in listening. They also had a notion that listening can be hardly acquired. Thus, new methods need to applied in listening activities, one of them is using YouTube. This study is classroom action research conducted in two cycles. The subjects of this study were 49 students of Akademi Kesehatan John Paul II Pekanbaru. Tests and Interviews were carried out to collect data. In cycle 1, the students’ score increased from 50 to 65.10. In cycle 2, the students obtained the average score of 71.02. In conclusion, the use of YouTube in listening activities can improve students’ listening skills. The result of interview revealed that students are more interested in learning English through YouTube. They can learn pronunciation and how to express ideas the same way native speakers did.